Continuous oral contraceptives versus long-term pituitary desensitization prior to IVF/ICSI in moderate to severe endometriosis: study protocol of a non-inferiority randomized controlled trial. Issue 1 (23rd February 2019) - van der Houwen, L E E; Lier, M C I; Schreurs, A M F; van Wely, M; Hompes, P G A; Cantineau, A E P; Schats, R; Lambalk, C B; Mijatovic, V
Abstract : What this means for patients Women with moderate to severe endometriosis receiving IVF or ICSI are nowadays advised to use a GnRH agonist during 3 months before IVF or ICSI in order to increase pregnancy rates. A GnRH-agonist treatment could be accompanied with unpleasant side effect such as hot flushes and vaginal dryness. In this study, we would like to investigate if pre-treatment with an oral contraceptive is as effective in pursuing pregnancy after IVF or ICSI with lower side effects and less costs. Abstract: STUDY QUESTIONS: The primary objective is to investigate if continuous use of oral contraceptives is non-inferior compared to long-term pituitary desensitization with a GnRH agonist prior to IVF/ICSI in patients with moderate to severe endometriosis with regard to treatment efficacy. Secondary objectives concern treatment safety and cost-effectiveness. WHAT IS KNOWN ALREADY: Long-term pituitary desensitization with a GnRH agonist for 3–6 months prior to IVF/ICSI improves clinical pregnancy rates in women suffering from endometriosis. However, discussion about this treatment strategy exists because of its uncomfortable side effects. Alternatively, IVF/ICSI pre-treatment with continuously administered oral contraceptives may offer fewer side-effects and lower (in)direct costs, as well as encouraging IVF outcomes in women with endometriosis. To date, these two different IVF/ICSI pre-treatment strategies in women with endometriosis have not been directly compared. STUDY DESIGN, SIZE, DURATION: An open-label, parallel two-arm randomized controlled multicenter trial is planned, including patients with moderate to severe endometriosis. To demonstrate an absolute difference of 13% (delta of 10% with non-inferiority margin of 3%) with a power of 80% 137 patients per group are sufficient. Taking into account a withdrawal of patients of 10% and a cancelation rate of embryo transfer after ovarian pick up of 10% (for instance due to fertilization failure), the sample size calculation is rounded off to 165 patients per group; 330 patients in total will be included. After informed consent, eligible patients will be randomly allocated to the intervention or reference group by using web based block randomization stratified per centre. Study inclusion is expected to be complete in 3–5 years. PARTICIPANTS/MATERIALS, SETTING, METHODS: The research population consists of patients with moderate to severe endometriosis (ASRM III/IV) who are scheduled for their first, second or third IVF/ICSI treatment attempt. Women aged over 41 years, younger than 18 years, with a known contraindication for the use of oral contraceptives and/or GnRH agonists or with severe male factor infertility will be excluded from participation. After informed consent patients are allocated to the intervention group (one-phase oral contraceptive continuously during three subsequent months) or the reference group (three Leuprorelin 3.75 mg i.m./s.c. depot injections during three subsequent months). Tibolon 2.5 mg can be given daily as add-back therapy in the reference group. After 3 months of pre-treatment the IVF/ICSI stimulation phase will be started. The primary outcome is live birth rate after fresh embryo transfer. Secondary outcomes are cumulative live birth rate after one IVF/ICSI treatment cycle (including fresh and frozen embryo transfers up to 15 months after randomization), ongoing pregnancy rate and time to pregnancy. In addition, treatment outcome parameters, adverse events, side-effects during the first 3 months, complications, recurrence of endometriosis (complaints), quality of life, patient preferences, safety and costs effectiveness will be reported. Measurements will be performed at baseline and at 3, 6, 9, 12 and 15 months after randomization. STUDY FUNDING/COMPETING INTEREST(s): All authors have no conflict of interest related to this manuscript. The department of reproductive medicine of the Amsterdam UMC location VUmc has received several research and educational grants from Guerbet, Merck and Ferring not related to the submitted work. TRIAL REGISTRATION NUMBER: The trial is registered as the COPIE trial (C ontinuous use of O ral contraceptives as an alternative for long-term P ituitary desensitization with a GnRH agonist prior to I VF/ICSI in E ndometriosis patients) in the Dutch Trial Register (Ref. No. NTR6357, http://www.trialregister.nl ). TRIAL REGISTRATION DATE: 16 March 2017. DATE OF FIRST PATIENT'S ENROLMENT: Enrollment is planned for November 2018.